Portfolio-Based Assessment - Zahiruddin Fitri, Abu Hassan; Joharry, Othman; Cheng, Sheila; Syamsul Nor Azlan, Muhammad; D'oria islamiah, Rosli; Angela Rumina, Leo (Academic Enhancement and Leadership Development Centre (ADeC), University of Malaya and Ministry of Education, Malaysia, 2018)
This book provides an overview of five categories of assessments namely peer and self-assessment, group-based assessment, performance-based assessment, portfolio and technology-based assessment. It also documents academic works, in the form of short case studies, in researching and practicing alternative assessments in their unique contexts to provide readers with ease of access and better understanding on application of alternative and innovative assessment. It is hoped that this book will spark interest and ideas that will inspire us to explore various innovative ways of assessing our students and will provide an excellent start to catalyse holistic assessment in our teaching and learning practices. Keywords: Educational Technology, Peer Assessment, Higher Education, Formative Assessment, Instructional Technology, Assessment in Higher Education, Online Learning, Learning And Teaching In Higher Education, E-Portfolios, Blended learning in higher education, Academic Performance, and Teaching and Learning In Adult and Higher Education